Layanan Konseling Individu Berbasis Islamic Cognitive Restructuring dalam Menangani Intensitas Akses Pornografi pada Remaja - Chika Lestari (Counseling As Syamil Jurnal Ilmiah Bimbingan Konseling Islam, 2026)
Pornography access among adolescents has become a growing psychosocial and spiritual concern in the digital era. Excessive exposure to pornographic content not only affects behavioral control but also disrupts cognitive processes, emotional regulation, and moral awareness. This study aims to examine the implementation of individual counseling services based on Islamic Cognitive Restructuring in addressing the intensity of pornography access among adolescents. Using a qualitative descriptive approach, data were obtained through observation of counseling processes, reflective field experiences, and analysis of relevant psychological and Islamic counseling literature. The findings indicate that Islamic-based Cognitive Restructuring effectively helps adolescents identify and modify distorted thoughts, strengthen self-control, and realign behavior with moral and spiritual values. By integrating cognitive restructuring techniques with Islamic principles such as muhasabah, tazkiyat al-nafs, and mujahadah al-nafs, the counseling process becomes more holistic and meaningful. This approach not only reduces the intensity of pornography access but also supports the development of psychological resilience and spiritual maturity among adolescents.